On local indeterminacy and endogenous cycles in Ramsey models with heterogeneous households - Bosi, Stefano (2009)
It is well-known that endogenous cycles can occur in Ramsey models with heterogeneous households and borrowing constraints. In this note, we address the issue of robustness in the more general case of endogenous labor supply and we explain the occurrence of local indeterminacy under progressive taxation.